2001
DOI: 10.1007/s004210100491
|View full text |Cite
|
Sign up to set email alerts
|

Mechanomyographic signals generated during unfused tetani of single motor units in the rat medial gastrocnemius muscle

Abstract: The aim of this study was to investigate mechanomyograms (MMGs) accompanying unfused tetani of fast fatigable (FF), fast fatigue-resistant (FR) and slow (S) motor units. Signals in the MMG were analyzed during tetanus, which was fused to a variable degree, evoked by electrical stimulation at three frequencies: 20, 40 and 80 Hz. Unfused tetani were characterized by an oscillating tension. Each oscillation in the tension of an unfused contraction was reflected by a parallel pressure wave signal in the MMG. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 23 publications
2
53
0
Order By: Relevance
“…An increased MMG amplitude of working muscle at the cessation of contraction was also recorded by others working on isolated muscle (Bichler 2000;Bichler and Celichowski 2001). The present results additionally shows that during the slow relaxation the increase was smaller than that during the fast relaxation in the BB and TB muscle, but was similar in the BR muscle.…”
Section: Mmg Amplitude During Slow and Fast Relaxationsupporting
confidence: 78%
See 1 more Smart Citation
“…An increased MMG amplitude of working muscle at the cessation of contraction was also recorded by others working on isolated muscle (Bichler 2000;Bichler and Celichowski 2001). The present results additionally shows that during the slow relaxation the increase was smaller than that during the fast relaxation in the BB and TB muscle, but was similar in the BR muscle.…”
Section: Mmg Amplitude During Slow and Fast Relaxationsupporting
confidence: 78%
“…Large MMG signals were observed during relaxation from fused and unfused tetani of isolated motor units in rats; MMG amplitude was dependent on the amplitude and velocity of tension changes (Bichler 2000;Bichler and Celichowski 2001). Because there is unfused muscle contraction during voluntary movements, MMG amplitude (MMG RMS) during relaxation from MVC might also depend on the amplitude and speed of force changes.…”
Section: Muscle Length and Electrical Activity Of Synergists And Antamentioning
confidence: 97%
“…The amplitude of the MMG signal is determined by the number of active motor units and their firing rates (Orizio, 1993;Orizio et al, 2003), and although not directly verified (Akataki et al, 2003), it has been suggested that the MMG frequency content qualitatively reflects the global firing rate of the unfused activated motor units (Akataki et al, 2001;Bichler, 2000;Bichler & Celichowski, 2001;Orizio, 1993;Orizio et al, 2003). Thus, examination of the MMG amplitude and mean power frequency vs. isometric torque relationships may provide information regarding the unique motor unit activation strategies (recruitment and firing rate) …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the MMG amplitude during repetitive stimulation reflects the magnitude of the fusion state of the muscle fiber (Bichler and Celichowski 2001a;Orizio 1993;Orizio et al 1996). As the fusion state of muscle fiber is caused by an inadequate fiber relaxation between impulses, its magnitude can be determined by the motor unit firing frequency and shortening and relaxation velocity of the activated muscle fibers.…”
Section: Introductionmentioning
confidence: 99%